Consequential effects of increased use of recycled fiber in the United States pulp and paper industry. (20th December 2019) - Chang, Jiyoun C.; Beach, Robert H.; Olivetti, Elsa A.
Abstract: Recycling is generally recognized as a key component of strategies to achieve improved resource efficiency and reduce the environmental burden associated with resource use. However, to maximize the net benefits offered by recycling, one must understand the system-wide effects of substituting primary materials with recycled materials and how those effects vary under alternative strategies. Consequential life cycle assessment (cLCA) approaches to evaluate the impact of increasing use of recycled materials require identification of grades and sources of scrap materials used at the margin. Various grades of recycled materials differ in their substitution possibilities and supply limits. However, most studies of cLCA for material recycling overlook these aspects and typically assume a fixed set of marginal activities. This study develops a model to describe the resource consumption behaviors of material producers and the resulting cascade of material flows for the case of the United States (US) pulp and paper industry. We observe that grades and sources of scrap materials used at the margin dynamically change so as the resulting environmental impact when demand for recycled containerboard products increases. The results show that the greenhouse gas (GHG) emission savings effect of using recycled materials can be considerably larger when marginal recovered fiber comes from additional recovery from landfill rather than being diverted from the export market. Also, the results show that the behavior of international trade partners for recovered paper may offset GHG emission savings from the domestic replacement of virgin pulpwood with recovered paper. Most importantly, such behaviors are dependent on grades used at the margin. The developed model and results can help inform the US pulp and paper industry, policymakers, and other stakeholders about the system-wide effects of increasing use of recovered paper. Highlights: We develop a model to describe resource consumption behaviors of the US pulp and paper producers and resulting fiber flows. This study suggests the importance of identifying the grade and source of scrap used at the margin in the recycling industry. CLCA based on static marginal technologies may not correctly quantify the system-wide effect of material recycling.